‘Quality’ as a governmental rationality in New Zealand wine - Russell Prince; Nicolas Lewis (EchoGéo)
The notion of ‘quality’ circulates around wine economy as it does many cultural economies. It may be possible to identify objective dimensions of quality in wine by referring to various aroma profiles, but it is both an inherently subjective and multiply qualified conception. In this paper, we begin from the position that one of the consequences of the widespread use and uncertain materiality of quality is that it defines a discursive field within which various technologies of control are brought to bear on the wine economy. We use the New Zealand case to argue that quality has been deployed to support the collective rents generated by a national reputation for quality wine and highlight key technologies developed to organise industry in the creation and support of that reputation. We suggest that as a governing rationality (governmentality) quality enacts an ethical economy associated with ownership of collective rents and a culture of wine that transcends its economy. The paper focuses attention on the work that quality performs in governing the New Zealand wine economy.